Coordinated Synthesis of Pigments Differing in Side Chain Length in Monascus purpureus and Investigation of Pigments and Citrinin Relation - Husakova, Marketa; Branska, Barbora; Patakova, Petra (Journal of agricultural and food chemistry, 2025)
The Monascus fungi have traditionally been used in Asia for food coloring. Unfortunately, the most well-known species, Monascus purpureus, very often produce mycotoxin citrinin in addition to pigments, which poses a significant problem for the use of pigments in foods. There is a step in pigment biosynthesis where a side chain of five or seven carbons is attached to the tetraketide, the product of polyketide synthase, resulting in the formation of pigments in pairs. Further, it is still unclear whether pigment and citrinin biosyntheses are related or independent. Therefore, this study is focused on the relationship between pigment and citrinin production and pigment analogues that differ in side chain length, all evaluated by the Spearman correlation test. To generate sufficient data, Monascus purpureus DBM 4360 was cultivated with different carbon and nitrogen sources and under osmotic stress induced by glucose and/or sodium chloride. The study reveals a very strong correlation between the production of five- and seven-carbon side chain pigments under all culture conditions tested for all three groups, yellow, orange, and red pigments. The correlation between pigments and citrinin depended on the group assessed and ranged from fair to very strong. While the coordinated synthesis of pigment analogues in pairs has been clearly confirmed, the relationship between pigment and citrinin production was unfortunately neither confirmed nor refuted and must be the subject of further research.
Keywords: pigments; Culture Techniques; Monascus purpureus; citrinin; Osmotic Pressure; regulation of secondary metabolites biosynthesis; kultivační techniky; Pigments, Biological; Carbon; uhlík; Citrinin; Nitrogen; dusík; Monascus; biologické pigmenty; stress conditions; osmotický tlak